(untitled) (Conference Zone, 2022)
The article scientifically analyzes the specifics of understanding national identity. The process of self-knowledge was recognized by scientists of the ancient and even modern world as a powerful force that plays an important role in the education of spirituality, the education of a perfect person. Self-consciousness is also one of the foundations of pure human morality. After all, every person who is a conscious member of society does not feel that he can use his position, his universal morality, if he does not know himself. However, the process of human self-realization is the result not only of personal action, but also of centuries-old philosophical thinking.